Eco friendly spectrophotometric method for quantitative estimation of lomefloxacin using hydrotropic approach - Ruchi Jain, Vaibhav Jain, Nilesh Jain, Deepak Kumar Jain, Surendra Jain (Journal of Applied Pharmaceutical Science)
The present work describes a novel, accurate, sensitive and economic safe spectrophotometric method was developed by application of hydrotropy, using 8 M Urea solution as hydrotropic solubilizing agent, for the quantitative determination of poorly watersoluble lomefloxacin HCl in tablet dosage form. There were more than 43 times enhancements in the solubility of lomefloxacin HCl increases in hydrotropic solution as compared to solubilities in distilled water. Lomefloxacin HCl shows maximum absorbance at 281 nm. Urea and other tablets excipents did not show any absorbance above 230 nm, and thus no interference in the estimation was seen. Lomefloxacin HCl was obeyed Beer,s law in the concentration range of 5 to 25μg/ml (r2= 0.9998) in hydrotropic solvent with mean recovery ranging from 98.03±0.65 to 98.59±0.32%. Proposed method is new, simple, economic, safe, rapid, accurate and reproducible. The developed methods were validated according to ICH guidelines and values of accuracy, precision and other statistical analysis were found to be in good accordance with the prescribed values. The method can be used for routine analysis in both research laboratories, and pharmaceutical and chemical industries to analyze the drugs without the use of organic solvents thus make the environment eco-friendly.
Keywords: Lomefloxacin HCl, Urea, Spectrophotometry, Eco-friendly, Hydrotropic.